2016
DOI: 10.1590/0103-8478cr20150856
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of gastric ulcers in horses exercised on a treadmill

Abstract: The most frequently causes of gastric ulcers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…In interpreting the above, it is important to distinguish between ESGD and EGGD as the majority of literature is weighted towards ESGD, and a recent study found no associations between owner-reported clinical signs and EGGD [ 63 ]. Similarly, there is other evidence to show that horses with gastric disease can show no signs at all [ 9 , 14 , 24 , 28 , 63 , 64 , 65 ] and some horses with signs do not display improvement of these signs with the resolution of gastric disease [ 56 ].…”
Section: Clinical Signsmentioning
confidence: 99%
“…In interpreting the above, it is important to distinguish between ESGD and EGGD as the majority of literature is weighted towards ESGD, and a recent study found no associations between owner-reported clinical signs and EGGD [ 63 ]. Similarly, there is other evidence to show that horses with gastric disease can show no signs at all [ 9 , 14 , 24 , 28 , 63 , 64 , 65 ] and some horses with signs do not display improvement of these signs with the resolution of gastric disease [ 56 ].…”
Section: Clinical Signsmentioning
confidence: 99%
“…Kolejne badanie zespołu pod kierownictwem Ribeiro [2016] dotyczyło wpływu treningu na bieżni na występowanie zmian wrzodowych w przewodzie pokarmowym. Do badania przystąpiły zdrowe konie; po odbytym okresie treningu stwierdzono, że wszystkie konie miały zmiany wrzodowe o różnej ilości i różnym nasileniu.…”
Section: Wrzody Jako Choroba Cywilizacyjna Koniunclassified
“…Fatores como confinamento, estresse, jejum, alimentação, manejo, ritmo intenso de treinamento ou administração de alguns medicamentos, como drogas antiinflamatórias não esteroides, são elementos que predeterminam sua ocorrência. Alimentos utilizados na suplementação de animais de esporte predispõem-se a úlceras gástricas em equinos, principalmente relacionados à ácidos graxos voláteis (AGV) decorrentes da fermentação desses alimentos (PALMA-DALLA et al, 2007;RIBEIRO et al, 2016). Quando estes animais secretam ácido gástrico continuamente e não recebem o alimento de forma contínua, a mucosa do estômago fica exposta a estes ácidos.…”
Section: Comprometimento Gastrointestinalunclassified